Exposure of Aspergillus flavus NRRL 3357 to the Environmental Toxin, 2,3,7,8-Tetrachlorinated Dibenzo-p-Dioxin, Results in a Hyper Aflatoxicogenic Phenotype: A Possible Role for Caleosin/Peroxygenase (AfPXG) - Hanano, Abdulsamie; Almousally, Ibrahem; Shaban, Mouhnad (Frontiers in Microbiology, 2019)
Aflatoxins (AF) as potent food contaminants are highly detrimental to human and animal health. The production of such biological toxins is influenced by the environmental factors including the pollutants, such as dioxins. Here, we report the biological feedback of an active AF-producer strain of A. flavus upon in vitro exposure to the most toxic congener of dioxins, the 2,3,7,8-tetrachlorinated dibenzo-p-dioxin (TCDD). The phenotype of TCDD-exposed A. flavus was typified by a severe limitation in vegetative growth, activation of conidia formation and a significant boosting in AF production. Furthermore, the level of reactive oxygen species (ROS) in fungal protoplast were increased (3.1 to 3.8-fold) in response to TCDD exposure at 10 and 50 ng mL-1, respectively. In parallel, superoxide dismutase (SOD) and catalase (CAT) activities were respectively increased by a factor of 2 and 3. In contrast to controls, transcript, protein and enzymatic activity of caleosin/peroxygenase (AfPXG) were also significantly induced in TCDD-exposed fungi. Subsequently, fungal cells accumulated 5-fold more lipid droplets (LDs) than controls. Moreover, the TCDD-exposed fungi exhibited 2-fold higher levels of AFB1. Interestingly, TCDD-induced hyperaflatoxicogenicity was drastically abolished in the AfPXG-silencing strain of A. flavus suggesting a role for AfPXG in fungal response to TCDD. Finally, TCDD-exposed fungi showed an increased in vitro virulence in terms of sporulation and AF production. The data highlight the possible effects of dioxin on aflatoxicogenicity of A. flavus and suggest therefore to paid a particular attention to the potential consequences of the climate change on the global food safety.